A "turn-on" silver nanocluster based fluorescent sensor for folate receptor detection and cancer cell imaging under visual analysis1. Issue 59 (28th July 2015) - Jiang, Hong; Xu, Gang; Sun, Yimin; Zheng, Weiwei; Zhu, Xiangxiang; Wang, Baojuan; Zhang, Xiaojun; Wang, Guangfeng
<x xml:space="preserve">Abstract</x> A novel terminal protection based label-free and "turn-on" fluorescent sensor for detection of folate receptors (FRs) and HeLa cells is developed by fluorescence resonance energy transfer (FRET) between single-walled carbon nanotubes (SWCNTs) and silver nanoclusters (AgNCs).